Engineering Strategies in Microorganisms for the Enhanced Production of Squalene: Advances, Challenges and Opportunities - Gohil, Nisarg; Bhattacharjee, Gargi; Khambhati, Khushal; Braddick, Darren; Singh, Vijai (Frontiers in Bioengineering and Biotechnology, 2019)
The triterpenoid squalene is a natural compound that has demonstrated an extraordinary diversity of uses in the pharmaceutical, nutraceutical, and personal care industries. Emboldened by this range of uses, novel applications that can profit from the benefits of squalene as an additive and supplement are expanding, resulting in increasing demand. The primary source has been from deep-sea shark liver, although recent declines in their populations and justified animal conservation and protection regulations have encouraged researchers to identify a novel route for squalene biosynthesis. This renewed scientific interest has profited from immense developments in the synthetic biology, which now allows for a wider range of plants, fungi, and microorganisms to be fine-tuned for the improved squalene production. There are numerous naturally producing species and strains; although they generally do not make commercially viable yields as the primary shark liver sources can deliver. The recent advances made towards improving the squalene output from natural and engineered species have inspired this review. Accordingly it will cover the in-depth knowledge offered by the studies of the natural sources, and the various biological and synthetic biology-based strategies that have been used to drive the improvements in the pathways towards large-scale production. The wide uses of squalene are also discussed, as well as notably its recent developments in anti-cancer applications and in augmenting influenza vaccines for greater efficacy.